Coaching for innovation : tools and techniques for encouraging new ideas in the workplace - Bianchi, Cristina (Palgrave Macmillan, 2014)
"Making innovation in the workplace highly accessible, Coaching for Innovation presents a practical step-by-step guide to coaching. Full of models, tips, exercises, and examples, this book provides readers with the tools to maximise creativity and performance in the workplace and to manage innovation options. It demonstrates the integral role that coaching can play in idea generation and the innovation process, to gain the competitive edge"--